Cimetidine inhibits production of interferon gamma and tumor necrosis factor alpha by splenocytes in aplastic anemic mice - Xia Tian; Wang Qi-Ru; Xu You-Heng (Acta Pharmacologica Sinica, 2016)
Aim: To study the effects of cimetidine (Cim) on the production of interferon gamma (IFN gamma) and tumor necrosis factor alpha (TNF alpha) by splenocytes in immune-derived aplastic anemic (AA) mice. Methods: Aplastic anemic mice model was constructed first, and then the splenocytes were induced to secrete IFN gamma and TNF alpha. Concentration of IFN gamma was assayed using sandwich ELISA, while that of TNF alpha was measured with L929 cytotoxicity methods. Results: (1) Concentrations of IFN gamma and TNF alpha secreted by splenocytes from AA mice were (137 +/- 36) ng/L and (6 +/- 3) microg/L, respectively, much more than the irradiated and the control mice. (2) Treatment with Cim 10 micromol/L reduced the concentrations of IFN gamma and TNF alpha to (14 +/- 8) ng/L and (2.7 +/- 0.6) microg/L, respectively. Conclusion: Cim could effectively reduce the production of IFN gamma and TNF alpha from splenocytes of AA mice.